A review of hydrogen generation methods via aluminum-water reactions - Nicola Musicco; Marcello Gelfi; Paolo Iora; Matteo Venturelli; Nancy Artioli; Luca Montorsi; Massimo Milani (International Journal of Thermofluids, 2025)
This article presents a comparison of the various methodologies reported in the literature to generate hydrogen through the reaction between aluminum powders and water. This reaction, however, is hindered by the surface oxide layer, which prevents direct contact between pure aluminum and water. The low cost of aluminum, its infinite recyclability, and the potential to carry out the reaction in an environmentally sustainable manner make it a promising material for hydrogen production. Given the critical need to address the limitations of hydrogen storage and transportation, as well as to accelerate the adoption of hydrogen as an energy carrier for the energy transition, this comparison focuses on the two most environmentally promising methodologies: ball milling and steam oxidation methodologies.